The influence of local economic development in poverty alleviation within Lepelle-Nkumpi Local Municipality, South Africa - Selemela, Charles; Mathebula, Ntwanano (Jurnal Administrasi Publik (Public Administration Journal), 2025)
The focus of this paper is to evaluate the influence of local economic development (LED) in poverty alleviation in municipalities using Lepelle-Nkumpi Local Municipality as a case paper. LED is essential as it involves identifying and using primarily local resources and skills to ensure or stimulate local economic growth and community development. Municipalities are responsible to ensure the promotion of LED initiatives to alleviate poverty. This paper was motivated by fact that there is lack of promotion of LED projects, high rate of poverty and unemployment and other socio-economic related issues that is occurring in communities within Lepelle-Nkumpi Local Municipality. Although the Municipality is continuing with the implementation of LED strategy but high rate of poverty and unemployment persist. Lack of capacity, incorrect interpretation or implementation of LED and resource constrains are some of the factors that contribute to failure of LED implementation in municipalities even though they are policies or guidelines in place. LED implementation in Lepelle-Nkumpi Local Municipality is constraints by many factors which hinder it to achieving economic development and poverty alleviation. The Municipality have challenges such as lack of budget, political interference in the allocation of LED projects, double dipping of projects, dependency syndrome of LED projects, LED strategies which do not address socio-economic challenges of communities, absence of monitoring and evaluation. Local economic development must contribute effectively on poverty alleviation and should have strong social focus.